Inclusiveness of Access Policies to Maternity Care for Migrant Women Across Europe: A Policy Review - Pařízková, Alena; Clausen, Jette Aaroe; Balaam, Marie-Clare; Haith-Cooper, Melanie; Roosalu, Triin; Migliorini, Laura; Kasper, Anne (Maternal and child health journal, 2024)
INTRODUCTION: Despite the interconnectedness of the European Union, there are significant variations in pregnant women's legal status as migrants and therefore their ability to access maternity care. Limited access to maternity care can lead to higher morbidity and mortality rates in migrant women and their babies. This study aimed to investigate and compare maternal health access policies and the context in which they operate across European countries for women who have migrated and are not considered citizens of the host country. METHODS: The study adopted a mixed-methods research design exploring policies on migrant women's access to maternity care across the migration regimes. Data were extracted from legal documents and research reports to construct a new typology to identify the inclusiveness of policies determining access to maternity care for migrant women. RESULTS: This study found inconsistency in the categorisation of migrants across countries and significant disparities in access to maternity care for migrant women within and between European countries. A lack of connection between access policies and migration regimes, along with a lack of fit between policies and public support for migration suggests a low level of path dependency and leaves space for policy innovation. DISCUSSION: Inequities and inconsistencies in policies across European countries affect non-citizen migrant women's access to maternity care. These policies act to reproduce structural inequalities which compromise the health of vulnerable women and newborns in reception countries. There is an urgent need to address this inequity, which discriminates against these already marginalised women.
Keywords: Obstetrics; těhotenství; Europe; Structural inequalities; Maternal health care access; zdravotní politika; Evropa; Migrant women; Transients and Migrants; osoby s přechodným pobytem a migranti; Infant, Newborn; ženské pohlaví; novorozenec; Humans; Pregnancy; European policies; Maternal Health Services; porodnictví; Health Policy; Inclusion; Female; služby zdravotní péče o matku; lidé